Calendula Officinalis L. in the Conditions of the Khorezm Oasis, Organization of Plantations (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
In the modern economy, medicinal plant resources are strategic in nature and are used as raw materials for the production of medicines that ensure public health and life. The production of medicinal plant raw materials provides opportunities to preserve its natural resources by collecting wild plants, growing them on an industrial scale, and creating large plantations [3].